Interpretive ability of vocalist-performers: essence and components - Ohanezova-Hryhorenko, Olha; Nosulia, Anatolii; Yu, Xing; Zehao, Guan; Qiwei, Hua (Cadernos de Educação Tecnologia e Sociedade, 2024)
The article reveals the essence of the interpretation of vocal works, examines the concept of the activity of a performing musician, its properties and qualities. It is shown that the interpretation of any musical work in any conditions (performance, concert performance, studio recording, etc.) requires the vocalist to have a deep understanding of the author’s intention, the ideas of the composer and the poet, and, accordingly, the possibility of their high-quality translation to the audience through the voice as his creative apparatus. It was concluded that the breadth of interpretation of musical works by different performers is determined by a complex combination of a number of factors, the main of which should be considered the level of preparation of the performer of musical works and the level of his cultural perception of music as a whole, which implies certain properties that are defined in the article as aspects of vocalist’ interpretive ability.